The girl who married a skull and other African stories : a cautionary fables + fairytales book - Spike, 1978-; Ashwin, Kate; McDonald, Kel; Stotts, Taneka, 1982- (Iron Circus Comics, 2018)
Presents fifteen graphic novel adaptations of African fables and fairy tales. Each tale is drawn by a different artist.